Three regimes, one Roof: an integrated substance-testing framework for PBJT, final income tax, and VAT on digital accommodation platforms in Indonesia - Dhian Adhetiya Safitra; Debby Tamara Tambunan (Educoretax, 2026)
Indonesian tax law assigns a single economic activity—providing the temporary use of a building—to three different regimes depending on its substance: the Specific Goods and Services Tax (PBJT) on hospitality services, a local government object; Final Income Tax (PPh Final) on land and/or building leasing, a central object; and Value-Added Tax (VAT) on the rental of taxable commercial space, also a central object. The boundaries between these regimes were designed to be mutually exclusive, yet digital accommodation platforms such as Airbnb, Traveloka, and Agoda generate hybrid arrangements that blur them, producing classification disputes, double taxation risk, and revenue leakage between central and local governments. Using a normative-juridical method grounded in legal certainty theory, the Stufenbau doctrine of normative hierarchy, and the substance-over-form principle, this study pursues three objectives: (1) to analyze the normative criteria that legally separate the three regimes under Law No. 1 of 2022 (HKPD Law), Government Regulation No. 34 of 2017, and Minister of Finance Regulation No. 70/PMK.03/2022; (2) to evaluate the potential revenue shifting and leakage caused by boundary ambiguity on digital accommodation platforms through an illustrative fiscal scenario; and (3) to formulate an integrated Substance-Testing Guideline jointly usable by the Directorate General of Taxes (DGT) and Regional Revenue Agencies (Bapenda) to harmonize enforcement. The analysis finds that the governing statutes are substantively coherent and non-contradictory; the three decisive criteria are the nature of the service (passive space versus active hospitality), the duration of occupancy (the one-month threshold), and the identity of the counterparty and lessor status. Misclassification is therefore primarily an administrative rather than a legislative problem, and a shared substance test—operationalized as a weighted indicator checklist with a clear decision tree and a joint DGT–Bapenda data-matching protocol—offers a practical path to harmonized enforcement.